Stellar mass-metallicity relation throughout the large-scale structure of the Universe: CAVITY mother sample - Domínguez-Gómez, Jesús; Perez, Isabel; Ruiz-Lara, Tomas; Peletier, Reynier F.; Sanchez-Blazquez, Patricia; Lisenfeld, Ute; Bidaran, Bahar; Falcon-Barroso, Jesus; Alcazar-Laynez, Manuel; Argudo-Fernandez, Maria; Blazquez-Calero, Guillermo; Courtois, Helene; et al. (Astronomy and astrophysics, 2023)
Context. Void galaxies are essential for understanding the physical processes that drive galaxy evolution because they are less affected by external factors than galaxies in denser environments, that is, in filaments, walls, and clusters. The stellar metallicity of a galaxy traces the accumulated fossil record of the star formation through the entire life of the galaxy. A comparison of the stellar metallicity of galaxies in various environments, including voids, filaments, walls, and clusters can provide valuable insights into how the large-scale environment affects the chemical evolution of the galaxy.Aims. We present the first comparison of the relation of the total stellar mass versus central stellar metallicity between galaxies in voids, filaments, walls, and clusters with different star formation history (SFH) types, morphologies, and colours for stellar masses between 10(8.0) to 10(11.5) solar masses and redshift 0.01 < z < 0.05. We aim to better understand how the large-scale structure affects galaxy evolution by studying the stellar mass-metallicity relation of thousands of galaxies, which allows us to make a statistically sound comparison between galaxies in voids, filaments, walls, and clusters.Methods. We applied non-parametric full spectral fitting techniques (pPXF and STECKMAP) to 10 807 spectra from the SDSS-DR7 (987 in voids, 6463 in filaments and walls, and 3357 in clusters) and derived their central mass-weighted average stellar metallicity ([M/H](M)).Results. We find that galaxies in voids have slightly lower stellar metallicities on average than galaxies in filaments and walls (by similar to 0.1 dex), and they are much lower than those of galaxies in clusters (by similar to 0.4 dex). These differences are more significant for low-mass (similar to 10(9.25) M-circle dot) than for high-mass galaxies, for long-timescale SFH (extended along time) galaxies than for short-timescale SFHs (concentrated at early times) galaxies, for spiral than for elliptical galaxies, and for blue than for red galaxies.